Azerbaijan - Raising Rates : Short-Term Implications of Residential Electricity Tariff Rebalancing - World Bank (Washington, DC, 2013)
Tariffs are low in Azerbaijan and need to be raised to finance badly needed network maintenance and to balance supply and demand. This study presents an analysis of the short-term impacts of a 50 percent electricity tariff increase on residential consumers. The study starts by reviewing electricity tariffs, consumption levels, and expenditure patterns compared to neighboring countries. It then considers the welfare effects o f raising tariffs, with particular attention to the poor and other vulnerable groups. It concludes with potential links to agriculture, the environment, and stakeholder analysis.